Flood Inundation Mapping and Spatial Analysis: A Case Study of the 2022 Massive Flood in Swat, Khyber Pakhtunkhwa, Pakistan - Ullah, Atta; Akbar, Saddique; Ghani, Muhammad Afan; Paryal, Muhammad; Maaz, Muhammad; Shah, Noman Ali; Momand, Imtiaz (MO.RI Publishing, 2025)
Climate change has increased the frequency of extreme precipitation, increasing rapid flood risks globally. This study integrates remote sensing, geospatial data and climatic statistics to map flood inundation and analyze precipitation patterns in Swat district, Khyber Pakhtunkhwa, Pakistan, following the 2022 flood. We used Google Earth Engine (GEE), applied supervised classification on sentinel-2 imagery achieving an accuracy of 99.7% for 2021 and 97.3% for 2022, confirming the precision of our analysis. Flood water body levels were meticulously scrutinized, culminating in the production of an illuminating flood inundation map through the Summer Permanent Water Bodies (SPWB) exclusion layer and Normalized Difference Flood Index (NDFI) framework. The NDVI and SPWB exclusion layer identified 1230 km2 of inundated area and 258 km2 of land use change in 2022. Analysis of Climate Hazards Group InfraRed Precipitation with Station (CHIRPS) summer precipitation data revealed a peak of 877 mm in 2022, with significant increase in southern, central and northern parts of Swat. This study is an earnest attempt to advance our understanding of flood mapping and offer roadmap for enhanced disaster management, supporting urban planning and mitigation strategies in the flood prone regions of Swat.